The adoption of generic immunosuppressant medications in kidney, liver, and heart transplantation among recipients in Colorado or nationally with Medicare part D. Issue 7 (31st March 2018) - Liu, Qian; Smith, Abigail R.; Park, Jeong M.; Oguntimein, Murewa; Dutcher, Sarah; Bello, Ghalib; Helmuth, Margaret; Turenne, Marc; Balkrishnan, Rajesh; Fava, Melissa; Beil, Charlotte A.; Saulles, Adam; et al.
Abstract : The transplant community is divided regarding whether substitution with generic immunosuppressants is appropriate for organ transplant recipients. We estimated the rate of uptake over time of generic immunosuppressants using US Medicare Part D Prescription Drug Event (PDE) and Colorado pharmacy claims (including both Part D and non‐Part D) data from 2008 to 2013. Data from 26 070 kidney, 15 548 liver, and 6685 heart recipients from Part D, and 1138 kidney and 389 liver recipients from Colorado were analyzed. The proportions of patients with PDEs or claims for generic and brand‐name tacrolimus or mycophenolate mofetil were calculated over time by transplanted organ and drug. Among Part D kidney, liver, and heart beneficiaries, the proportion dispensed generic tacrolimus reached 50%‐56% at 1 year after first generic approval and 78%‐81% by December 2013. The proportion dispensed generic mycophenolate mofetil reached 70%‐73% at 1 year after generic market entry and 88%‐90% by December 2013. There was wide interstate variability in generic uptake, with faster uptake in Colorado compared with most other states. Overall, generic substitution for tacrolimus and mycophenolate mofetil for organ transplant recipients increased rapidly following first availability, and utilization of generic immunosuppressants exceeded that of brand‐name products within a year of market entry. Abstract : Analysis of prescription drug event and claims data from transplant recipients shows that overall rates of generic substitution for tacrolimus and mycophenolate mofetil increased rapidly following first availability and that utilization of generic immunosuppressants exceeded that of brand‐name products within a year of market entry.